Phage therapy for Escherichia coli urinary tract infections: selecting therapeutic phages and understanding resistance mechanisms in urine - Park de la Torriente, Alba (The University of Edinburgh, 2024)
Urinary tract infections (UTIs) affect a large proportion of the human and canine population. Due to rising levels of antibiotic resistance, empirical treatment with conventional antibiotics may fail, which can increase the probabilities of recurrence and severe complications. The most common species causing UTIs is uropathogenic Escherichia coli (UPEC), from which a clonal complex of particular concern is the O25:H4-ST131 as it is associated with the global emergence of multidrug-resistant and highly pathogenic urinary tract and bloodstream infections. Phage therapy is regarded as a promising alternative to antibiotics and could be especially useful to treat multidrug- resistant bacteria such as ST131 strains. This work aimed to find phages that could target strain EC958: a well characterised member of the ST131 group; and to dissect the causes of resistance that could lead to unsuccessful treatment. First, the optimisation of an artificial urine (AU) that could be used to study the phage-bacterium interaction was carried out, with the intention of obtaining results that could be translated to human and veterinary medicine. Then, different phages and phage combinations were screened against EC958 in the AU and standard lab media (LB). Finding a phage cocktail that could inhibit EC958 in LB was relatively easy, whereas none of the combinations tested in AU could prevent its growth for more than 8 hours. To understand what was causing the resistance, the infection assays were analysed by media and by timepoint using the phage LUC4. For this, individual colonies were isolated from the surviving population after phage exposure and re-challenged with the phage. The majority of the resistant variants recovered from LB assays were insensitive to the phage in the subsequent infections, which indicated that they had a fixed resistance to the phage. In AU, two different phenotypes were found in the resistant population. Some of the single colonies gave rise to a fixed phage-resistant culture, and others were still susceptible to the phage, despite having survived the initial challenge. Analysis of short and long read sequencing data indicated that mutations led to loss of expression of the primary phage receptor—OmpC—in the fixed resistant variants. The transient resistance, which is also observed in pooled canine urine but not in LB, was accelerated when the bacteria were cultured in the supernatant of an EC958 culture, and this was not due to significant changes in the phage adsorption rate. It was concluded that the productive phage infection was highly dependent on the culture conditions and the physiological state of the bacterial culture, which validated the effort to develop the AU for E. coli-phage interaction studies. The mechanism underlying the transient resistance could not be fully deciphered in the time available, but various hypotheses are discussed in the thesis and are currently being tested. Towards testing phage therapy for E. coli ST131 UTIs, three pilot studies were carried out in pigs: the first one with the aim of testing the safety of therapeutic phages produced from a detoxified E. coli strain; the second to establish a porcine model of UTI with ST131, and the third one used the UTI model to observe the efficacy of the phage. This study was also useful to analyse a phage treatment of EC958 infection in vivo, and ex vivo, by challenging the infected urine samples with phage. Preliminary data from these pilot studies suggested that pigs can be a good model to study E. coli UTIs and phage therapy. The phage preparations did not cause any significant inflammatory response in the pigs. E. coli ST131 strain EC958 was able to colonise and establish a UTI after intravesical instillation, with some evidence of macroscopical lesions in the bladder mucosa such as petechias. However, it is speculated that the infection was starting to self-resolve after a week. Phage LUC4 showed little impact to treat the UTI in vivo, with only a very short-lived reduction in bacterial counts in the urine of one of two animals. In line with the in vitro studies using AU and pooled urine, analysis of the surviving bacteria showed that they retained sensitivity to phage LUC4 when tested under laboratory conditions. This indicated that transient resistance was also the main issue preventing an effective intervention in vivo, for which it is important to understand the mechanism behind this resistance in order to achieve a safe and effective phage therapy for a multidrug-resistant UPEC such as ST131 EC958.
Keywords: urinary tract infection; escherichia coli; bacteriophage; phage therapy; UPEC; phage-resistance; artificial urine; phage cocktail